Analysis of Mineral Composition of Alteration Rock in Warm Ground and Steaming Ground in Lahendong North Sulawesi Using Sem-Edx And Ftir - Wenas, Donny R.; Bujung, Cyrke A.N. (International Journal of Engineering and Technology, 2018)
This research is aimed to study the mineral composition of alterations rock in Lahendong geothermal manifestation area, North Sulawesi. This research is using Scanning Electron Microscopic-Energy Dispersive X-Ray Spectrometric (SEM-EDX) and Fourier Transform Infra Red (FTIR) characterization method. The result of the characterization using SEM-EDX shows that the warm ground contained the mineral silica, while the steaming ground contained the kaolinite clay. The rock elements of the warm ground consist of O 71.90% and Si 28.10% with O dominating, this is indicate that the rocks have high porosity, while the rock elements of the steaming ground consist of O 56.86%, Al 1.94%, Si 3.52% and C 7.25% is coating material sample for energy dispersive x-ray spectrometric as penetrate in this rock sample. This result is consistent with the characterization using FTIR.